Commitment to inform before electronic contracting in Libyan law - Maysoun Mukhtar Al-Jafari (International Journal of Law Research and Studies, 2025)
The electronic contract is one of the most important transactions that take place over the Internet today. Despite being a contract like any other contract, it takes on an electronic character according to the way in which it is concluded, which affects the integrity of the contractual balance between the seller and the consumer, who often concludes these contracts quickly to purchase goods or obtain services without physically inspecting the goods or the subject of the contract and verifying their integrity. Rather, he is satisfied with the information provided by the seller about these goods and services, which may expose him to fraud or deception through misleading advertisements. Since the consumer is the weak party in electronic contracts, it became necessary to provide guarantees to protect him and oblige the professional seller to inform him (described notification) to ensure the integrity of his will and obtain sound and informed satisfaction. Hence, legislation rushed to establish rules regulating the obligation to inform in the electronic contract. The Libyan legislator has headed in the same direction, as it issued Law No. (6) of 2022 regarding electronic transactions, which regulated the obligation to inform in form and substance, as well as the consequences of the seller’s breach of this obligation, which achieves cognitive balance between the seller and the buyer and avoids risks that threaten the stability of the contract.